Favorable response to PD-1 inhibitor plus chemotherapy as first-line treatment for metastatic gastric mixed neuroendocrine-non-neuroendocrine tumor: a case report - Zheng, Lingnan; Sun, Lingqi; Ma, Ji (Frontiers in Pharmacology, 2024)
A gastric mixed neuroendocrine-non-neuroendocrine tumor (MiNEN), a rare malignancy, has no standard treatment currently. Here, we report a patient with pathologically confirmed gastric MiNEN following radical surgery with rapid postoperative tumor distant recurrence. Immunofluorescence results suggested intensive lymphocyte infiltration in the tumor and programmed death receptor ligand 1 (PD-L1) immunohistochemistry 22C3 pharmDx assay showed TPS was 5% and CPS was 10. After 6 cycles of treatment with etoposide and cisplatin combined with toripalimab, the efficacy was assessed as complete response. Our report shows that for gastric MiNEN patients with high expression of PD-L1, chemotherapy combined with immune checkpoint inhibitors may achieve more significant efficacy.